2010
DOI: 10.3109/01443610903531394
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of cervical cancer seen in a tertiary health facility in Nnewi, south-east Nigeria

Abstract: Cervical cancer remains the commonest gynaecological cancer among women in the developing countries. The records of all the histologically confirmed cervical cancer patients managed in Nnamdi Azikiwe University Teaching Hospital, Nnewi, over a 5 year period were analysed for the clinical presentation and histological pattern of the malignancy. A total of 75 cases of cervical cancer were managed over the period giving an incidence of 65.2% of all gynaecological cancers and 13.4% of all gynaecological admissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 14 publications
(26 reference statements)
9
33
0
Order By: Relevance
“…This finding of late presentation is consistent with a study done in Lagos, Nigeria which found that less than 10 % of cervical cancer patients presented at operable stages with the majority presenting with advanced disease [11]. Similarly, a clinico-pathological analysis of cervical cancer seen in a tertiary health facility in south-eastern Nigeria found that 89.3 % of the patients presented at advanced stages [12]. Other related studies in northern Nigerian settings have documented advanced disease at presentation in 66 %–81 % of cervical cancer patients [13, 14].…”
Section: Discussionsupporting
confidence: 87%
“…This finding of late presentation is consistent with a study done in Lagos, Nigeria which found that less than 10 % of cervical cancer patients presented at operable stages with the majority presenting with advanced disease [11]. Similarly, a clinico-pathological analysis of cervical cancer seen in a tertiary health facility in south-eastern Nigeria found that 89.3 % of the patients presented at advanced stages [12]. Other related studies in northern Nigerian settings have documented advanced disease at presentation in 66 %–81 % of cervical cancer patients [13, 14].…”
Section: Discussionsupporting
confidence: 87%
“…Offensive vaginal discharge and weight loss were two other presenting complaints that occurred in about 40.0% of the cases in this study. Both of these complaints have been report with varying frequencies in association with cervical cancer 11,13–16,19…”
Section: Discussionmentioning
confidence: 99%
“…Should every case of abnormal vaginal bleeding be promptly investigated, cervical cancers would be diagnosed in early stages, at a time when there could be hopes of cure. However, due to the amalgamation of illiteracy, poverty, ignorance, non-utilization of screening services, and a host of others factors particular to the underserved in the poor rural communities of southeast Nigeria, the majority of the women present in late stage disease 11,13,15,16,19. Offensive vaginal discharge and weight loss were two other presenting complaints that occurred in about 40.0% of the cases in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average Nigerian woman seeks medical attention only when symptoms develop and usually long after the onset of symptoms. 11 This is more so when the sexual organs are involved. Many respondents complained that they fear the test will violate their privacy.…”
Section: Chigbu and Aniebuementioning
confidence: 99%